Analytical design of the fractional order controller and robustness verification - Vavilala, Sateesh K.; Thirumavalavan, Vinopraba (IAES International Journal of Robotics and Automation (IJRA), 2021)
This paper proposes a fractional order controller (FOC) for the level control problem of the coupled tank system, using the desired time domain specifications. The coupled tank system is used in the chemical industries for the storage and mixing of liquids. The FOC is designed analytically using the direct synthesis method. In the direct synthesis method, the Bode's ideal loop transfer function is chosen as the desired transfer function. Bode's loop transfer function has the advantages like robustness to system gain variations, constant phase and very high gain margin. Performance of the proposed controller is compared with the state of the art literature. Simulation results showed that the proposed controller has the least peak overshoot. The robust performance of the proposed controller is also the best. Robust stability of the system with the proposed controller is verified, and the system is found to be robustly stable.